Study of the biogas technology adoption as a livestock waste management among smallholder farmers in Indonesia. (May 2019) - Putra, A R S; Czekaj, T G; Lund, M
Abstract: The aim of this paper was to determine the factors influencing biogas adoption as a livestock waste management among smallholder farmers in Indonesia. The study emphasized the positive influence of farmer engagement on the technology transfer process. A cross-sectional survey was conducted in Yogyakarta Province, Indonesia by involving 351 respondents who were smallholder practicing the Mixed Crops and Livestock (MCL) farming from 2013 to 2014. The results of Logit regression showed that the biogas technology adoption in Indonesia was influenced by attainment of formal education, women involvement in decision making, number of cattle in the household, household's income, availability of biogas instalment funding, and the degree of connectedness to stakeholders in the agricultural technology transfer system. The study concluded that the availability of biogas installation funding and better engagement to the technology transfer stakeholders positively influenced the biogas technology adoption among MCL farmers.